INTEGRATING PAI VALUES INTO THE PROBLEM-BASED LEARNING MODEL TO STRENGTHEN RELIGIOUS CHARACTER - Setyani, Isni; Yahya, Muhamad Slamet (Jurnal Konseling Pendidikan Islam, 2026)
This study examines the integration of Islamic Religious Education values into the Problem-Based Learning (PBL) model as an effective pedagogical approach in shaping the religious character of students. The method used in this study is a literature review, which includes an analysis of literature related to the application of PBL and IRE values. The results indicate that through learning focused on contextual problem-solving, active participation, and reflection on Islamic values, students not only enhance their intellectual skills but also experience a deep internalization of spiritual values. The PBL model creates a collaborative, transformative, and meaningful learning environment, making the development of religious character a practical reality in daily life. Therefore, the systematic integration of PAI values and PBL is essential to address the challenges of character education in the complex and digital modern era.